2005
DOI: 10.1021/jp044946x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Solvent on the Surface-Enhanced Raman Spectra of Ruthenium(II) Bipyridyl Complexes

Abstract: In the present work a new dye, [Ru(dcbpyH2)2(bpy-TPA2)](PF6)2, and the well-known (Bu4N)2[Ru(dcbpyH)2(NCS)2] complex were investigated. The electronic transitions of both dyes showed solvatochromic shifts due to specific interactions of the ligands with the solvent molecules. The surface-enhanced Raman (SER) spectra of the dyes dissolved in water, ethanol, and acetonitrile were measured in silver and gold colloidal solutions. The results demonstrate that the dyes were adsorbed on the metallic nanoparticles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
2
43
0
1
Order By: Relevance
“…This view is consistent with the recent SERS study of N719 on colloidal nanoparticles. 29 It is noteworthy that the ν(NCS) bands are clearly observed at 2106, 2126, and 2076 cm , on Au, Ag, and Cu, respectively. From the SERS selection rule, 30 it was reported that the charge transfer (CT) mechanism could also significantly contribute the enhancement of the SERS intensities.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…This view is consistent with the recent SERS study of N719 on colloidal nanoparticles. 29 It is noteworthy that the ν(NCS) bands are clearly observed at 2106, 2126, and 2076 cm , on Au, Ag, and Cu, respectively. From the SERS selection rule, 30 it was reported that the charge transfer (CT) mechanism could also significantly contribute the enhancement of the SERS intensities.…”
Section: Resultsmentioning
confidence: 90%
“…The bands are strongly solvent dependent and consistent with the previous report. 29 The intraligand charge transfer band was observed at 308 nm when the process was performed in water. The metal ligand charge transfer bands were observed at 370 nm and 502 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In addition temperature-dependent interfacial vibrational spectroscopic tools can provide information on the energetics or phase transition of adsorbates on surfaces. [8][9][10] Despite several spectroscopic reports on Ruthenim (II) complexes, [11][12][13][14] there has not been either investigation on the spectroscopic study or the thermal degradation and the resulting change in molecular architecture in detail for a cyanoacrylic acid film fabricated on the TiO2 surfaces to the best of our knowledge. In this present work, temperature-dependent diffuse reflectance infrared Fourier-transform (DRIFT) spectroscopy was applied to understand the nature of adsorption and structural change of α-cyano-4-hydroxycinnamic acid (CHCA) on the TiO2 surfaces.…”
Section: Introductionmentioning
confidence: 99%